2014
DOI: 10.1037/a0035363
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral activation for depressed breast cancer patients: The impact of therapeutic compliance and quantity of activities completed on symptom reduction.

Abstract: Patient compliance with BA assignments is causally associated with depression reduction, whereas the quantity of completed activities is less relevant toward conceptualizing positive treatment outcome. Study findings are discussed in the context of behavioral models of depression and BA therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 60 publications
3
35
0
9
Order By: Relevance
“…The theoretically critical questions about whether therapy-induced activation and decreased avoidance mediate symptomatic improvement have only been investigated in a few studies . Some researchers have used single case designs to investigate the temporal relations between the proposed mechanisms and outcome (Gaynor & Harris, 2008;Manos, Kanter & Lou, 2011;Folke et al, 2015) and others have investigated the correlation between client compliance with activation assignments and outcomes (e.g., Busch, Uebelacker, Kalibatseva & Miller, 2010;Folke et al, 2014;Hershenberg, Paulson, Gros & Acierno, 2014;Ryba, Lejuez & Hopko, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The theoretically critical questions about whether therapy-induced activation and decreased avoidance mediate symptomatic improvement have only been investigated in a few studies . Some researchers have used single case designs to investigate the temporal relations between the proposed mechanisms and outcome (Gaynor & Harris, 2008;Manos, Kanter & Lou, 2011;Folke et al, 2015) and others have investigated the correlation between client compliance with activation assignments and outcomes (e.g., Busch, Uebelacker, Kalibatseva & Miller, 2010;Folke et al, 2014;Hershenberg, Paulson, Gros & Acierno, 2014;Ryba, Lejuez & Hopko, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Self-reported activation obtained through the BADS-SF likely captures activation caused by other factors in a client’s life (e.g., increased activity due to non-mental health intervention). Previous research has used the proportion or percent completion of ideographically designed homework assignments as a measure of personalized activation in BA treatment (Ryba et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Recent BA research has lent additional support. Ryba, Lejuez, & Hopko (2014) conducted a post-hoc analysis of the causal relationship between structured activities (i.e., quantity of activities and proportion of activities completed) and depression. The authors concluded that although the specific quantity of completed activities was not causally related to reductions in depression, participant compliance with assigned activities was causally associated with improvements.…”
mentioning
confidence: 99%
“…La EROS ha sido utilizada en investigaciones relacionadas con estados de ánimo bajos o diagnósticos de depresión (Barraca-Mairal, 2010;Carvalho et al, 2011;Gawrysiak, Nicholas, & Hopko, 2009); además, de ser un instrumento necesario para medir noción de refuerzo medioambiental en investigaciones relacionadas con el consumo de tabaco y sustancias (Daughters, Magidson, Schuster, & Safren, 2010;MacPherson et al, 2010), problemas de personalidad y trastornos esquizofrénicos (Daughters, Sargeant, Bornovalova, Gratz, & LeJuez, 2008;Gamero, Vucinovich, & Oñate, 2011), desarrollo de tareas en niños (Busch et al, 2009) y pacientes con problemas afectivos debido a enfermedades médicas como el cáncer (Carvalho & Hopko, 2009;Carvalho et al, 2011;Ryba, LeJuez, & Hopko, 2014).…”
unclassified